Singapore. - Department, International Monetary Fund. Monetary and Capital Markets (IMF Staff Country Reports., 2013)
Singapore: Detailed Assessment of Observance-Assessment of Observance of the CPSS-IOSCO Principles for Financial Market Infrastructures.